Solitary myofibroma in children: a report of two cases - Coşkun, Çağrı; Kösemehmetoğlu, Kemal; Ayvaz, Mehmet; Vargel, İbrahim and Aydıngöz, Üstün and Özcan, Hatice Nursun and Varan, Ali and Yalçın, Bilgehan (The European Research Journal, 2024)
Myofibromas are rare benign tumors of myofibroblasts, seen more commonly in children. These tumors typically involve soft tissues with a predilection for the head and neck. Malignant neoplasia is often suspected for these rapidly growing tumors in early childhood. Clinical and radiological findings are not typical, and histopathological examination makes the definitive diagnosis. This pathology requires the intervention of a multidisciplinary team and regular follow-up. We report our experience with two children with myofibromas, one in the right arm of a 5-year-old girl and the other in the right axilla of a 9-year-old boy. Tumors were totally resected in both children, who are under follow-up with no adjuvant treatment free of disease after surgery. Myofibroma should be considered in the differential diagnosis of pediatric soft tissue tumors. Surgical resection is sufficient for treatment and patients should be followed regularly for possible recurrences.